1997
DOI: 10.1093/jac/40.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of resistance to metronidazole and clarithromycin in Helicobacter pylori clinical isolates from Spain

Abstract: The aim of this study was to determine the frequency of resistance to amoxycillin, tetracycline, metronidazole and clarithromycin in 282 Helicobacter pylori clinical isolates from Spain and to evaluate the evolution of resistance over the five years of this study. The overall percentage of resistance was 19.9% for metronidazole and 3.5% for clarithromycin. Resistance to metronidazole rose from 9% in 1991 to 21.6% in 1995, although 33.3% resistance was found in 1993. Clarithromycin resistance was not detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 7 publications
2
36
1
Order By: Relevance
“…These Tc r determinants are often associated with transmissible genetic elements such as plasmids, transposons and integrons (8). In the case of H. pylori, Tc r is not observed as frequently as in other species (17,19,23). However, tetracycline-resistant H. pylori isolates have started to emerge, and their prevalence is increasing, especially in Asian countries such as China, Korea, and Japan (15,16,26).…”
mentioning
confidence: 99%
“…These Tc r determinants are often associated with transmissible genetic elements such as plasmids, transposons and integrons (8). In the case of H. pylori, Tc r is not observed as frequently as in other species (17,19,23). However, tetracycline-resistant H. pylori isolates have started to emerge, and their prevalence is increasing, especially in Asian countries such as China, Korea, and Japan (15,16,26).…”
mentioning
confidence: 99%
“…In adults, the rate of resistance of H. pylori to clarithromycin before treatment is largely less, amounting to 0 to 10% in European and North American countries, averaging 1% in The Netherlands, 3.5% in Spain, 5% in Ireland, and 6% in the United States, with the highest rate (10%) occurring in France (3,12,20). This disparity in resistance rates seems to be correlated to the national level of macrolide consumption, since a crossover resistance mechanism among different types of macrolides develops rapidly (3).…”
mentioning
confidence: 99%
“…Furthermore, in many reports, study populations are too small, both overall and for each year examined, to allow meaningful conclusions to be reached. This is the case for many studies that show possible increased rates of CLA resistance [2][3][4]. While some larger studies have also demonstrated increasing trends in CLA resistance in Europe [5] and the USA [6], others showed no such increase [7,8].…”
Section: In October 2005 Robert Warren and Barrymentioning
confidence: 97%